Semirotational Tree Factorizations of Complete Graphs - Petrenyuk, A. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We select the class of so-called semisymmetric trees and prove that every tree T from this class admits a T-factorization of a special form in the case where T is of order n = 2k ≤ 16. We formulate the conjecture that every semisymmetric tree T admits a T-factorization. We establish the existence of a T-factorization for semisymmetric trees of certain classes.